Verrucous carcinoma of foot: a diagnostic enigma - Kotera, Sai Suraj; K., Manjunath; S., Rajagopalan (International Surgery Journal, 2016)
We present two cases of Verrucous Carcinoma (VC) of the foot in middle aged men. This is a rare locally invasive, well differentiated and low grade squamous cell carcinoma (SCC) with Human Papilloma Virus as a possible causative agent. It follows a chronic course and mimics various skin lesions which lead to delay in diagnosis by up to 15 years. The diagnosis is made histologically and treatment is wide local excision. Though at 1 year follow up showed no signs of recurrence. Due to confusion of diagnosis in the early stage, there will be delayed diagnosis. So early pathological diagnosis and intervention are key determinants for better prognosis.